Find all School-related info fast with the new School-Specific MBA Forum

 It is currently 26 Apr 2015, 13:30

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# gmatprept1q19

Author Message
TAGS:
Director
Joined: 23 May 2008
Posts: 840
Followers: 3

Kudos [?]: 37 [0], given: 0

gmatprept1q19 [#permalink]  20 Jun 2009, 16:51
00:00

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 0 sessions
Attachments

gmatprept1q19.jpg [ 23 KiB | Viewed 807 times ]

Current Student
Joined: 03 Aug 2006
Posts: 116
Followers: 4

Kudos [?]: 141 [0], given: 3

Re: gmatprept1q19 [#permalink]  20 Jun 2009, 18:31

Asking at what two points does the graph of $y = (x+a)(x+b)$ intersect the x-axis?
i.e. when x=? when y=0.

$\Rightarrow (x+a)(x+b) = 0$

$\Rightarrow x(x+b)+a(x+b) = 0$

$\Rightarrow x^2 + xb+ ax + ab = 0$

$\Rightarrow x^2 + x(a+b) + ab = 0$

We need to know $a+b=?$ and $ab=?$ to answer the question.

Looking at Statement 1

$1. a+b=-1$

$\Rightarrow x^2 + (-1)x + ab = 0$

we still don't know $ab=?$

Hence Insufficient.

2. The graph intersects the x-axis at (0,-6)

i.e when x=0, y=-6

$y = (x+a)(x+b)$

$\Rightarrow -6 = (0+a)(0+b)$

$\Rightarrow -6 = ab$

Plugging in this value into

$x^2 + x(a+b) + ab = 0$

$\Rightarrow x^2 + x(a+b) - 6 = 0$

We are now missing the value for $(a+b)$

Hence Insufficient

Looking at Statement 1 and 2 together gives us

$(a+b)=-1$ and $ab=-6$

Plugging into

$x^2 + x(a+b) + ab = 0$

$\Rightarrow x^2 - x - 6 = 0$

We can now solve for x. Hence both statements together are sufficient. The answer is C
Re: gmatprept1q19   [#permalink] 20 Jun 2009, 18:31
Display posts from previous: Sort by

# gmatprept1q19

 Powered by phpBB © phpBB Group and phpBB SEO Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.